The Utility of Chromosomal Microarray Analysis in Developmental and Behavioral Pediatrics - Beaudet, Arthur L. (2013)
Chromosomal microarray analysis (CMA) has emerged as a powerful new tool to identify genomic abnormalities associated with a wide range of developmental disabilities including congenital malformations, cognitive impairment, and behavioral abnormalities. CMA includes array comparative genomic hybridization (CGH) and single nucleotide polymorphism (SNP) arrays, both of which are useful for detection of genomic copy number variants (CNV) such as microdeletions and microduplications. The frequency of disease-causing CNVs is highest (20%–25%) in children with moderate to severe intellectual disability accompanied by malformations or dysmorphic features. Disease-causing CNVs are found in 5%–10% of cases of autism, being more frequent in severe phenotypes. CMA has replaced Giemsa-banded karyotype as the first-tier test for genetic evaluation of children with developmental and behavioral disabilities.